Factionalism in Iban Politics - Lucy, Sebli-Seidelson (UNIMAS Publisher, 2013)
The Schism among the Iban takes root in the historical animosity that exist within them due largely to geographical factor; leading to the mergence of two dominant Iban groups, the Saribas and the Rejang Basin Ibans. Apart from historical animosity, the split within the Iban community; i.e. systematic marginalization by the state, lack of education attainment, parochialism and the 'divisive' role of Chinese elites. All these factors have contributed to ongoing factionalism within the Iban community, resulting in the continued decline of Iban political power.